Sustainability: measuring social responsibility - Boguski, Terrie; Boguski, Rebecca (Kansas State University, 2011)
In his book, The Triple Bottom Line, Andrew Savitz highlights the need to evaluate human decisions and activities from the perspective of environmental, economic, and social sustainability. In the late 1960’s, methods for evaluating the life cycle environmental impacts of products and services were beginning to be formulated. This work led to the current methods and standards for conducting environmental Life Cycle Assessment (LCA) studies. LCA is a recognized method for evaluating the long-term environmental impacts of human decisions and actions. Likewise, standard methods have been developed for measuring life cycle costs of products and services through Life Cycle Cost Analysis (LCCA). In recent years, more attention has been given to social sustainability. In 2009, the UNEP SETAC Life Cycle Initiative published guidelines for Social Life Cycle Assessment (S-LCA), outlining a framework and best-practices for assessing the social and socio-economic impacts of product life cycles. Many companies have independently developed and published their own social responsibility performance goals and measures. Currently, there is no commonly accepted standard for evaluating social sustainability. This presentation discusses the author’s research in the area of social sustainability, highlighting common themes and indicators, as well as difficulties with definitive measurements.
Keywords: Life Cycle; Sustainability; Social